Bonds, Bondholders Protection and Asset Allocation of Multimarket Funds - Thayse Machado Guimarães; Rodrigo Fernandes Malaquias (BBR: Brazilian Business Review)
This paper aims to create a bondholders’ protection index (BPI) and to investigate what the influence of this index would be on multimarket funds’ allocation in corporate bonds. Understanding this relation is relevant because only about 1.36% of multimarket funds’ portfolios correspond to debentures. This study advances the literature by covering a topic little discussed in a Brazilian context, proposing the creation of a BPI, which would be related to the number of automatic maturity clauses, which guarantee immediate payment to bondholders in cases of the rupture of a contract. This research comprised 926 debentures series issued in Brazil from 2009 to 2017, and 1,753 multimarket funds, which allocated some portfolios’ percentage in these securities. In creating the BPI, we contemplated 15 restrictive clauses, which the most common correspond to negligent business performance, liquidation, dissolution and bankruptcy, and restrictions related to company structure. Moreover, we examined less common restrictive clauses as well, including indebtedness policy, shares issuance and amortization, and ratings downgrading. Regarding data analysis, we employed multiple linear regression models, with pooled estimators, applying the standard error correction by White’s robust matrix (1980). The main results suggest that BPI positively effects multimarket funds’ allocation in debentures. Furthermore, this influence is more intense in indentures with higher number of clauses with automatic maturity. Thus, this study contributes to literature about restrictive clauses, since it demonstrates that debentures’ flexible and adaptable structure seems to be interesting for the main bondholders in Brazil.